El sector nuclear en Argentina: tramas productivas y desarrollo tecnológico - García, Marisa Cecilia; Lugones, Manuel; Reising, Ailin María (Universidad Nacional de Córdoba, 2016)
Fil: García, Marisa Cecilia. Universidad Nacional del Comahue. Fundación Bariloche; Argentina.